Factors Affecting Quality of Life of Emergency Room Doctors and Nurses in Public and Private Hospitals Affected by COVID-19 in the Eastern Economic Corridor Area - นวลละออง, พัชร์วลีย์ (Journal of Health Science of Thailand, 2022)
The purpose of this research was to study the factors affecting the quality of life of emergency room physicians and nurses in public and private hospitals affected by COVID-19 in the Eastern Economic Corridor (EEC) area. Data were collected by interviewing doctors and nurses during the second wave of outbreaks from June to August 2021. The target informants were divided into 2 groups: (1) emergency room physicians, and (2) emergency room nurses who performed both full-time and temporary contract work in emergency rooms during COVID-19 outbreaks. The study tools were questionnaire to collect information and opinions of the informants with regard to their perception and opinions on current situation factors that affect the quality of work life. The data were analyzed by using both descriptive and inferential statistics. There were 472 samples selected. It was found that the factors affecting the quality of life of doctors and emergency room nurses in public and private hospitals affected by COVID-19 in the EEC area included the support from patients which resulted in the treatment success, the psychological factors which was the pride in in taking care of patients and keeping them out of danger; the physical factors associated with risky situation, heavy work load, and delaed compensation. Based on the study results, hospital administrators and agencies should consider providing more support to improve the quality of life of physicians and nurses; and develop models to enhance the quality of life of personnel working in emergency room departments during the COVID-19 outbreak.